Rethinking The Role of Indigenous Law Community in Managing Indigenous Forest in Jambi Province - Taufik Yahya; Fauzi Syam (Jambe Law Journal, 2018)
This paper examines the synchronization of legal regulations in forestry, green farming, and mining sectors along with their implementation regulations. The certainties of the existence of customary law community in Legal Acts No. 41 year 1999 concerning Forestry does not give certainties for customary law community in managing forest in Indonesia. Meanwhile, Legal Acts No. 6 year 2014 about Village stresses out that there is a specific acknowledgement about local customary village as a part of Customary Law Community. In the Legal Acts about Village, the establishment of Customary Law Community is strongly stated in provincial government regulations. This paradox has brought a bad consequence to customary forest that is managed by customary law communities in Jambi province.